Dynamics of Legal Politics of Judicial Power in Responding to the Industrial Revolution 4.0 - Boy Nurdin (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze how the justice system and judicial power in Indonesia adapt to technological developments in the Industrial Revolution 4.0 era. This study uses a qualitative method with a normative legal approach that examines laws and regulations, legal doctrines, and judicial practices related to the application of technology in the law enforcement process. The main focus of this study is to identify the challenges and opportunities that arise for the judiciary in the digital era, such as changes in decision-making, the use of technology for judicial transparency, and the protection of human rights amidst legal automation. The results of the study indicate that digitalization and the application of technology in the Indonesian judicial system are very important to improve the efficiency, transparency, and accessibility of justice. Structural changes due to the amendments to the 1945 Constitution resulted in the decentralization of judicial power with three independent institutions: the Supreme Court, the Constitutional Court, and the Judicial Commission. Initiatives such as e-court and e-litigation implemented by the Supreme Court facilitate the legal administration process, while the Constitutional Court introduces a transparent judicial system through an informative website and mobile application. The Judicial Commission also utilizes digital platforms to maintain independence and accountability. However, challenges include the digitalization of the judicial process, demands for transparency, the influence of artificial intelligence, and increasing legal literacy. Courts need to adapt to technology to increase efficiency while protecting personal data and upholding human rights principles.